Выражения. 1. 8–(y+4)(y–4). 2. (3b+5c)(5c–3b) + 9b^2 3. 9x(2–x)+(3x+2)^2. 4. 4(x^2+4)–(5x–4)^2. 5. 3(x+y)^2–6xy. 6. (x–3)^2–(x+3)(3–x).

belozerovyurik belozerovyurik    1   03.09.2019 10:20    1

Ответы
Nastya060104sataeva Nastya060104sataeva  06.10.2020 14:28
1. 8–(y+4)(y–4)=8-(y²-16)=8-y²+16=-y²+24
2. (3b+5c)(5c–3b) + 9b^2=(5c+3b)(5c-3b)+9b²=25c²-9b²+9b²=
25c²
3. 9x(2–x)+(3x+2)^2=18x-9x²+9x²+12x+4=
30x+4
4. 4(x^2+4)–(5x–4)^2=4x²+16-(25x²-40x+16)=4x²+16-25x²+40x-16=
-21x²+40x
5. 3(x+y)^2–6xy=3(x²+2xy+y²)-6xy=
3x²+6xy+3y²-6xy=3x²+3y²
6. (x–3)^2–(x+3)(3–x)=x²-6x+9-(3+x)(3-x)=
x²-6x+9-9+x²=2x²-6x
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра